Oxidized phospholipids are biomarkers, drug targets, and drug leads - Oskolkova, Olga V.; Birukova, Anna A.; Birukov, Konstantin G.; Bochkov, Valery N. (Frontiers in Drug Discovery, 2022)
Enzymatic oxidation or autooxidation of esterified polyunsaturated fatty acids (PUFA) residues within phospholipids in cell membranes or circulating lipoprotein particles leads to the formation of a broad range of oxidized phospholipid (OxPL) species. Chronically elevated OxPL levels present in circulation and atherosclerotic plaques are thought to induce proinflammatory and injurious effects on blood- and vessel wall cells. However, analysis of the structure-activity relationship also identified specific OxPL products exhibiting prominent anti-inflammatory, pro-survival and barrier protective properties. This minireview will briefly summarize rapidly accumulating evidence pointing to the importance of OxPLs in pathology, where they can play multiple roles of biomarkers, drug targets and drug leads.